miR-212/132-Enriched Extracellular Vesicles Promote Differentiation of Induced Pluripotent Stem Cells Into Pancreatic Beta Cells - Bai, Chunyu; Ren, Qiwei; Liu, Haifeng; Li, Xiangchen; Guan, Weijun; Gao, Yuhua (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic beta cell transplantation is the ideal method for treatment of type 1 diabetes mellitus (T1DM), and the generation of beta cells from induced pluripotent stem cells (iPSCs) of patients is a promising strategy. In this study, we improved a previous strategy to produce beta cells using extracellular vesicles (EVs) derived from mature beta cells and differentiated beta cells from iPSCs (i-Beta cells), which secreted insulin under glucose stimulation in vitro and ameliorated hyperglycemia in vivo. Mechanistic analyses revealed that EV-carried microRNA (miR)-212/132 (EV-miR-212/132) directly bound to the 3ʹ UTR of FBW7 to prevent its translation and FBW7 combined with NGN3 to accelerate its proteasomal degradation. EV-miR-212/132 stabilized NGN3 expression to promote differentiation of endocrine cells from induced iPSCs. Moreover, NGN3 bound to PDX1 to enhance transcription of endogenous miR-212/132 and formed a positive regulatory circuit that maintained the functions of mature pancreatic beta cells. Conclusions: This study describes a novel approach for beta cell production and supports the use of iPSCs for cell replacement therapy of T1DM.